How to build a purpose-guided life - Dodge, Bryan; Dodge Development (Duncanville, Tex. : Dodge Development, 2003)
Addresses questions including: How can finding purpose save your life, how do you know what your purpose is in life, how to position your life so purpose can show itself, why doesn't everyone find his or her purpose, learning that finding purpose is a choice, how can we clear the way to a purpose guided life, why do we find purpose and then lose it?
Keywords: Self-actualization (Psychology); Motivation (Psychology); Achievement motivation; Audiobooks